Proposal of public policy regarding the integration of financial education classes in Romania - Baia Olimpia Georgiana (Technium Social Sciences Journal, 2020)
This policy highlights the importance of financial literacy, the ability to make healthy financial decisions in regards to debt, credit and other expenses, serious matters in this Digital Age. Being financially literate in today’s economic climate is more important than ever. Understanding finances can help individuals make better money management decisions, budget money properly, adequately save for college, and be financially prepared for retirement. Romania has the lowest number of companies per capita, most of the existent companies are not financially active and rarely do make a profit, which is a concerning statistic for a state member of the European Union. The general objective of this public policy is to integrate financial literacy classes into the Romanian educational curriculum.